1997
DOI: 10.1002/(sici)1097-4598(199706)20:6<651::aid-mus1>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of inflammatory myopathies

Abstract: The treatment of the immune‐mediated inflammatory myopathies remains largely empirical. Corticosteroids are usually effective in polymyositis and dermatomyositis but may need to be combined with methotrexate or azathioprine in some patients. Intravenous immunoglobulin (IVIg) is effective as add‐on therapy in some patients not adequately controlled with steroids or immunosuppressive agents, but further controlled trials of IVIg are necessary to define the indications and optimal dose regimens. Cyclophosphamide,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 77 publications
1
31
0
2
Order By: Relevance
“…We identified that patients who received steroids exhibited an impressive improvement in their symptoms (71.4%; p=0.023) reinforcing the most favorable outcome achieved with steroid treatment [10,11]. The percentage of patients treated with methotrexate was higher than previous study (57% of our patients compared with 34% in other study [54]).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…We identified that patients who received steroids exhibited an impressive improvement in their symptoms (71.4%; p=0.023) reinforcing the most favorable outcome achieved with steroid treatment [10,11]. The percentage of patients treated with methotrexate was higher than previous study (57% of our patients compared with 34% in other study [54]).…”
Section: Discussionsupporting
confidence: 74%
“…Modalities of treatment used for IIM: steroids, methotrexate, azathioprine, cyclophosphamide, chlorambucil, intravenous immunoglobulin (IVIG), and rituximab as the approved treatment for IIM [10,11]. The course and outcome of the disease: the outcome of patients was classified into respondent and resistant.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reviews have discussed the practical aspects of managing ongoing therapy and have emphasized the importance of not continuing high doses of steroids for too long and balancing this against not tapering the dose too quickly. They advocate the introduction of an immunosuppressive agent such as methotrexate, azathioprine, or mycophenolate earlier rather than later as a steroid-sparing strategy [34,[38][39][40][41]. Oral pulse therapy with dexamethasone (monthly cycles of 40 mg/ day for 4 consecutive days) has been suggested as an alternative to prednisolone and has been shown to be as effective in a RCT and to have a more favorable side effect profile, but the time to relapse was shorter with dexamethasone [42].…”
Section: Conventional Therapiesmentioning
confidence: 99%
“…Este resultado vem ao encontro de outros estudos em doenças neuromusculares e em doenças do colágeno com envolvimento muscular, em que as alterações encontradas pelos diversos autores são consideradas inespecíficas, podendo ocorrer em casos de lesões das fibras musculares de diversas etiologias 49,50 . A simples deposição, ou a presença desses complexos imunes, não é suficiente para determinar a lesão podendo não ter relação com os achados anatomopatológicos 49,[51][52][53] .…”
Section: Macrófagounclassified